(3YeOI GdCMcGe Yf SjO GdGfGes - (3YHO GdZfj Hf YHO GdhGMO Hf Ydj Hf SQhQ GdebOSj GdLeGYjdj GdOeTbj GdMfHdj, CHh eMeO, Jbj GdOjf,J (B600 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdMeO ddg Gdedc GdLHGQ , GdhGMO GdbgGQ , hCTgO Cf dG Edg EdG Gddg CeG HYO , aEf HYV GdENhGf SCdfi GNJUGQ LedI ef CMGOjK GdCMcGe eeG EJab Ydjg GdEeGeGf s
(3BNQgG (B:s
(3ef cJGH (B( (3GdYJb (B) (3bhdg (B: ( (3aHGYg HKeGf eGFI OQge Ke CQSd Kefg Edjg hgPG BNQ GdcJGH HJeGeg hceGdg , hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfhGfGJ HGMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B275s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
Keywords: (3GdMOjK h GdeUWdMs